Nano-strategies targeting cancer-associated fibroblasts to enhance immunotherapy and reverse resistance - Xu, Juqing; Chen, Ze; Qin, Yi; Tan, Lu; Xu, Shaohui (Frontiers in Immunology, 2025)
Cancer-associated fibroblasts (CAFs) are significant contributors to the establishment of the immunosuppressive tumor microenvironment (TME) and pose a significant challenge to the effectiveness of successful immunotherapy. CAFs can secrete cytokines, chemokines, and extracellular matrix components; inhibit the invasion of immune cells; promote regulatory cell populations; and induce T cell exclusion phenotypes, thereby lowering the effectiveness of immune checkpoint inhibitors (ICIs). With the development of the field of nanotechnology, increasing studies have paid attention to employing nano-strategies to specifically control and target CAFs. These nanoplatforms can transport therapeutic cargos, e.g., CAF-toxic chemicals, signal regulators, or phenotype-modifying agents, precisely to CAFs, respectively, lowering systemic toxicity. Furthermore, the combination therapy of CAF-targeting nanoparticles and immune checkpoint inhibitors had, in preclinical scenarios, the synergistic effect of promoting T cell infiltration, antigen presentation, and cytotoxicity. However, heterotypic CAF subpopulations, inconsistency of different cancer models, inefficient cargo delivery, and translatability constraints in the clinic are serious challenges. Development of multifunctional and stimulus-active nanomedicine has great potential to overcome these challenges. Initial clinical trials, including fibroblast activation protein (FAP)-targeted CAR-T cells and antibody-drug conjugates, highlight the increasing translational potential of CAF-targeted nano-immunotherapy. This review summarizes the current progress in CAF-targeted nano-immunotherapy, emphasizing that a comprehensive molecular understanding and thorough clinical validation are essential for facilitating its clinical application in the treatment of solid malignancies.